(untitled) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Múltiplos Olhares Vol. 1, n. 2 (2011) Link de acesso ao número http://portaldeperiodicos.eci.ufmg.br/index.php/moci/issue/view/96